2016
DOI: 10.1073/pnas.1603718113
|View full text |Cite
|
Sign up to set email alerts
|

Origin and evolution of developmental enhancers in the mammalian neocortex

Abstract: Morphological innovations such as the mammalian neocortex may involve the evolution of novel regulatory sequences. However, de novo birth of regulatory elements active during morphogenesis has not been extensively studied in mammals. Here, we use H3K27ac-defined regulatory elements active during human and mouse corticogenesis to identify enhancers that were likely active in the ancient mammalian forebrain. We infer the phylogenetic origins of these enhancers and find that ∼20% arose in the mammalian stem linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
89
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(124 citation statements)
references
References 57 publications
23
89
0
Order By: Relevance
“…3; Supplemental Table S2). Together, our differential histone state analysis results are broadly supported by several studies that have consistently suggested a high degree of regulatory element conservation between closely related species in metazoans (Cotney et al 2013;Boyle et al 2014;Prescott et al 2015;Emera et al 2016). We note that the estimated fraction of conserved CRE is lower (36.2%: 39.6% of promoters and 24.3% of enhancers) when analyses are not restricted to six-way orthologous regions (i.e., treating all human CREs lacking an ortholog in any of the other species as not conserved).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…3; Supplemental Table S2). Together, our differential histone state analysis results are broadly supported by several studies that have consistently suggested a high degree of regulatory element conservation between closely related species in metazoans (Cotney et al 2013;Boyle et al 2014;Prescott et al 2015;Emera et al 2016). We note that the estimated fraction of conserved CRE is lower (36.2%: 39.6% of promoters and 24.3% of enhancers) when analyses are not restricted to six-way orthologous regions (i.e., treating all human CREs lacking an ortholog in any of the other species as not conserved).…”
Section: Resultssupporting
confidence: 86%
“…Similarly, the recruitment of novel regulatory networks in the uterus was likely mediated by ancient mammalian TEs (Lynch et al 2011(Lynch et al , 2015. Conversely, neocortical enhancers do not exhibit strong evidence of transposon co-option (Emera et al 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work suggests that TEs can extensively remodel regulatory networks that are involved in specific processes including dosage compensation 103 , immunity 44 , and early embryonic development 24 . Other comparative studies of enhancer evolution in the liver 148 and the neocortex 149 among mammals found only a minor contribution for host co-option of TE activity. These observations raise the question of whether TE-mediated regulatory evolution may be inherently biased for certain biological processes, or if it is a more general mechanism for large-scale genetic innovation.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 89%
“…Distal enhancers are rapidly evolving (Villar et al, 2015). In mammals, their origin often involves exaptation of ancestral DNA (Villar et al, 2015) or de novo emergence from neutral genomic background (proto-enhancers) (Emera et al, 2016). The finding of only a couple of conserved cis-regulatory elements, located in the vicinity of SOX21 and HMX3 genes, across eumetazoans Royo et al, 2011) underscores the dynamic nature of enhancer sequence evolution.…”
Section: Evolution Of Enhancer Elementsmentioning
confidence: 99%